2019
DOI: 10.1177/2158244019876285
|View full text |Cite
|
Sign up to set email alerts
|

“Playing Mother”: Channeled Careers and the Construction of Gender in Academia

Abstract: Gender discrimination in the academy globally is widely recognized in terms of faculty ranking and career progression rates. U.K. national data notes the lower research recognition of women scholars as well as gendered pay gaps. This article reports on a qualitative study of women academics across discipline groups at a British post-1992 corporate university. Focus group discussion findings suggest that gendered career pathways are implicated in hindering the career progression of women academics. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 47 publications
2
26
0
1
Order By: Relevance
“…Previous studies have found that students have higher expectations of female faculty regarding nurturing and emotional support (Malisch et al, 2020;Sprague & Massoni, 2005). Students are more likely to turn for help to female academics, who are expected to be warmer, more empathetic, and have greater interpersonal skills (Ashencaen Crabtree & Shiel, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have found that students have higher expectations of female faculty regarding nurturing and emotional support (Malisch et al, 2020;Sprague & Massoni, 2005). Students are more likely to turn for help to female academics, who are expected to be warmer, more empathetic, and have greater interpersonal skills (Ashencaen Crabtree & Shiel, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, researchers have discovered that the process of "the projectification of academia" (Ylijoki, 2016, Abstract) and increased dependence on third-party research funding negatively impact the chances of female academics securing funding for their projects (Ahlqvist et al, 2015;Herschberg, 2018). The increasing global corporatization and commodification of HEIs, the reframing of students as customers, and the growing importance of student evaluations have a growing impact on the career advancement of faculty (Ashencaen Crabtree & Shiel, 2019;Dobija et al, 2019;Kloot, 2004;Probert, 2005), with discriminatory results for female staff (MacNell et al, 2015). Ashencaen et al (2019) observe that students expect male instructors to be objective and female instructors to be warm and possess good interpersonal skills.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Most women academics, compared to male colleagues, are concentrated in the lower hierarchical ranks where career progression is constrained (Ashencaen Crabtree and Shiel 2018). The extant research evidence suggests that academic women are more likely to undertake less valorised academic tasks: teaching and administration, as opposed to elite research-focused pathways (Eddy and Ward 2015;Ashencaen Crabtree and Shiel 2019), garnering greater career rewards.…”
Section: Introductionmentioning
confidence: 99%